ANALYSIS OF JOB TRAINING, WORK MOTIVATION AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT CLASS II A CORPORATE INSTITUTIONS, BATAM CITY - Ismoyo, Riky; Indrayani, Indrayani; Khaddafi, Muammar (RADJA PUBLIKA, 2022)
Performance of employees is important thing in something organization / agency. The capabilities possessed by the source power man naturally no free from a number of factor important pusher. Purpose study this is for knowing influence training work, motivation work and culture organization to performance employee at the Class II A Penitentiary of Batam City. Analysis used that is analysis associative, trait study this is quantitative, analysis multiple linear regression and analysis coefficient determination with use IBM SPSS 22 program assistance. Population in study this is whole employee institution correctional class II A Batam City, while the sample is with use formula slovin so obtained 95 respondents. Results obtained from study this showing that : 1) Training Work take effect significant by Partial on Employee Performance in Class II A Penitentiary in Batam City , 2 ) Motivation Work take effect significant by Partial on Employee Performance in Class II A Correctional Institutions in Batam City , 3) Culture Organization take effect significant by Partial on Employee Performance in Class II A Correctional Institutions in Batam City , 4) Training Work , Motivation Work and Culture Organization take effect significant by simultaneous on Employee Performance in Class II A Penitentiary in Batam City . Adjusted R square value 0, 699 could called coefficient determination, thing this means 0, 699 (69, 9 %) Employee Performance could obtained and explained by Training Work, Motivation Work and Culture Organization whereas the rest by 31.1% explained by variable outside the model that is not researched.